2020
DOI: 10.15419/bmrat.v7i8.621
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pre-treatment routine hematological parameters in breast carcinoma: Advantageous or deleterious?

Abstract: Introduction: The most common malignancy which endangers the quality of life in females is breast cancer. It is also the major public problem in society and despite advances in treatment strategies, it still leads to high mortality. In all breast cancer patients, the first assessment done before surgery is the complete blood count (CBC). There exists a strong relationship between immune response of the body and clinical staging of breast cancer. This study aimed to determine the most reliable hematological mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…This finding is similar to the study conducted in Ethiopia, which showed that the prevalence of thrombocytopenia was 23.5% [21]. In contrast to this study, a study conducted in Switzerland revealed that thrombocytosis was increased throughout the treatment [11]. This variation could be due to the sample size, clinical characteristics, and socio-demographic differences between the study groups.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is similar to the study conducted in Ethiopia, which showed that the prevalence of thrombocytopenia was 23.5% [21]. In contrast to this study, a study conducted in Switzerland revealed that thrombocytosis was increased throughout the treatment [11]. This variation could be due to the sample size, clinical characteristics, and socio-demographic differences between the study groups.…”
Section: Plos Onesupporting
confidence: 83%
“…Pretreatment hematological abnormalities are mostly due to suppression of hematopoiesis via bone marrow infiltration [8,9]. Several studies confirm that pretreatment anemia, neutropenia, and thrombocytopenia were found to be common in breast cancer patients [10,11]. The post-treatment hematological abnormalities are associated not only with the malignant cell effect, but also with the chemotherapy and radiotherapy medications administered to the patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is in agreement with studies reported from India; they concluded that the levels of Hgb, WCC, RCC and PLT counts significantly altered in the HIV-infected patients when compared with the HCs 22 23. Changes in the haematological indices might be due to the effects of the infections on the blood cells 24 25. Comparable findings were reported in Turkey26 27 and Egypt 28.…”
Section: Discussionsupporting
confidence: 92%
“…( 25 ) also revealed that eosinophils are involved in the immune response to breast tumors. Various studies also reported that platelets release chemokines in response to drug toxicity and increase eosinophil counts through chemicals (eosinophils activating factor, Platelet P-selectin) released from platelets ( 34 , 35 ). These chemicals inhibit Eosinophils apoptosis and prolong survival ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%